Kesadaran Caregiver tentang Resiko Jatuh pada Lansia (Caregiver Awareness about the Risk of Falling in the Elderly) - Prabasari, Ninda Ayu; Manungkalit, Maria (JURNAL NERS LENTERA, 2020)
Introduction: In the aging process, the elderly experience loss of motor skills in movement. With this change, the ability of the elderly to react to falls has decreased resulted in the occurrence of falls experienced. Caregiver support in fall prevention is needed. The purpose of the literature review is to review the caregiver's awareness of the risk of falling in the elderly. Method: Issues, methodologies, similarities and differences in research are the basis for implementing a literature review. Of the 7 studies, there are five studies using quantitative and two studies using a qualitative approach. The population is all caregivers who care for the elderly and the sample used is some or all caregivers who play a role in elderly care. Result: Based on 7 studies, there were five studies that showed that caregivers had good awareness in preventing the risk of falling in the elderly and there were two studies that provided information that caregivers had less awareness in falling prevention in the elderly. Discussion: With the existence of health education, health promotion even with training provided to caregivers will be able to help caregivers in implementing fall prevention measures for the existing elderly. Key words: caregiver, elderly, fall